The differential effects of task difficulty on the perception of passing distance and subsequent passing action in a field hockey push pass task - Paterson, G.; van der Kamp, J.; Bressan, E.; Savelsbergh, G. (Acta Psychologica, 2019)
The aims of the study were to initially investigate whether the perceived distance of a field hockey push pass task was influenced by manipulating task difficulty (Experiment 1), and further, expanding on the research, whether perceptual biases would translate into the execution of a corresponding push pass action (Experiment 2). Based on predictions from the two-visual systems model, we hypothesized that the action-specific perceptual biases in distance perception would not translate into the control of movement. In Experiment 1, elite field hockey players estimated the distance from targets that differed in size before making push pass actions toward the target (i.e., the smaller targets being more difficult). Results showed that participants did estimate the perceived distance of the push pass task to be larger as a function of task difficulty. We found a similar result in Experiment 2, and in addition, manipulated the required outcome of the push-pass while measuring the speed of the push-pass and found that a perceptual bias did not translate into the execution of the actual push pass task (Experiment 2). In line with the action-specific account of perception, a perceptual bias arose that may assist in making adaptive action choices. However, consistent with the two-visual systems model, this perceptual bias did not affect subsequent control of movement, preventing it from becoming maladaptive. Implications for talent identification and development are briefly discussed